Self‐employed But Looking: A Labour Market Experiment. (13th November 2014) - Koellinger, Philipp D.; Mell, Julija N.; Pohl, Irene; Roessler, Christian; Treffers, Theresa
<x xml:space="preserve">Abstract</x> We examine whether having previously been self‐employed is a negative signal on the job market. In a UK field experiment where two applications of otherwise equally qualified individuals were sent out in response to the same vacancies in human resource management, we find that entrepreneurs systematically receive fewer responses than non‐entrepreneurs. Empirical studies that treat market wages as the opportunity cost of remaining self‐employed are therefore likely to overestimate alternative earnings to entrepreneurship.